(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
: Acute kidney injury is the leading cause of nephrology consultation and is associated with high mortality rates. The primary causes of AKI include ischemia, hypoxia or nephrotoxicity. An underlying feature is a rapid decline in GFR usually associated with decreases in renal blood flow. Inflammation represents an important additional component of Acute kidney injury leading to the extension phase of injury, which may be associated with insensitivity to vasodilator therapy. It is suggested that targeting the extension phase represents an area potential of treatment with the greatest possible impact. This article provides information on the methods of identifying pathomorphological lesions in the kidneys of offspring born under conditions of chronic poisoning in the mother.